Fast Switching Electrochromic Devices Containing Optimized BEMA/PEGMA Gel Polymer Electrolytes. (7th October 2013) - Garino, N.; Zanarini, S.; Bodoardo, S.; Nair, J. R.; Pereira, S.; Pereira, L.; Martins, R.; Fortunato, E.; Penazzi, N.
Abstract : An optimized thermoset gel polymer electrolyte based on Bisphenol A ethoxylate dimethacrylate and Poly(ethylene glycol) methyl ether methacrylate (BEMA/PEGMA) was prepared by facile photo-induced free radical polymerisation technique and tested for the first time in electrochromic devices (ECD) combining WO3 sputtered on ITO as cathodes and V2 O5 electrodeposited on ITO as anodes. The behaviour of the prepared ECD was investigated electrochemically and electro-optically. The ECD transmission spectrum was monitored in the visible and near-infrared region by varying applied potential. A switching time of ca. 2 s for Li + insertion (coloring) and of ca. 1 s for Li + de-insertion (bleaching) were found. UV-VIS spectroelectrochemical measurements evidenced a considerable contrast between bleached and colored state along with a good stability over repeated cycles. The reported electrochromic devices showed a considerable enhancement of switching time with respect to the previously reported polymeric ECD indicating that they are good candidates for the implementation of intelligent windows and smart displays.